2017
DOI: 10.1155/2017/5846290
|View full text |Cite
|
Sign up to set email alerts
|

Toothpick inside the Common Bile Duct: A Case Report and Literature Review

Abstract: The incidence and prevalence of foreign body (FB) ingestion are difficult to estimate. Unlike other foreign bodies, the ingestion of a toothpick is very uncommon and carries high morbidity and mortality rates. We report a case of a 73-year-old female patient presenting mid-term epigastric pain. Abdominal ultrasound revealed a slightly dilated common bile duct (CBD) and magnetic resonance showed an irregular filling failure in distal CBD and gallstones. Endoscopic Retrograde Cholangiopancreatography revealed ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Intrabiliary migration of foreign bodies is a rare complication and the literature only consists of case reports. Besides surgical clips, nonabsorbable sutures, coils for arterial embolization, ingested fish bones and toothpicks, and remnants of draining tubes or stents have been reported to migrate into the biliary tract [6, 7, 8]. A literature review of 69 cases of intrabiliary migrated surgical clips showed ERCP to be the appropriate treatment, with a success rate of 85% [9].…”
Section: Discussionmentioning
confidence: 99%
“…Intrabiliary migration of foreign bodies is a rare complication and the literature only consists of case reports. Besides surgical clips, nonabsorbable sutures, coils for arterial embolization, ingested fish bones and toothpicks, and remnants of draining tubes or stents have been reported to migrate into the biliary tract [6, 7, 8]. A literature review of 69 cases of intrabiliary migrated surgical clips showed ERCP to be the appropriate treatment, with a success rate of 85% [9].…”
Section: Discussionmentioning
confidence: 99%
“…Foreign bodies ingestion can sometimes be difficult to diagnose. Patients most commonly present either with bowels obstruction or with complications related to perforation, migration, and intraabdominal fistulas . Patients will report a history of recurrent abdominal pain, fever of unknown origin, like our patient, nausea, obstipation, diarrhea etc.…”
Section: Discussionmentioning
confidence: 96%
“…The patient's age, mental capabilities, clinical characteristics, and socioeconomic status should also raise questions. The surgeon should be prepared for life‐threatening situations such as major vascular involvement , as well as highly specialized and technically challenging procedures if the toothpick involves the hepatic hilum for instance .…”
Section: Discussionmentioning
confidence: 99%
“…The frequent lodging sites of fishbones in the upper digestive tract are palatine tonsil, base of the tongue, valleculae, the piriform sinus and the first narrow area of esophagus [5]. It has been reported in a case that a toothpick was inserted into the common bile duct [6], but fishbone inserted into the duodenal papilla was never reported. Since the fishbone in our case was long and thin and very similar to a toothpick, we speculated that the fishbone might also be inserted into the common bile duct.…”
Section: Discussionmentioning
confidence: 99%
“…Some foreign bodies may cause acute pancreatitis [9], while others may lead to ascending cholangitis [10]. In addition, at the acute stage, some foreign bodies might be misdiagnosed as choledocholithiasis [6]. At the chronic stage, some foreign bodies might form biliary stones, which may cause the cholangitis [11] or cholecystitis [12].…”
Section: Discussionmentioning
confidence: 99%